Periprosthetic bone mineral density around uncemented titanium stems in the second and third decade after total hip arthroplasty: a DXA study after 12, 17 and 21 years - Peitgen, David S.; Innmann, Moritz Maximilian; Merle, Christian; Gotterbarm, Tobias; Moradi, Babak; Streit, Marcus R. (Calcified tissue international, 2018)
Implant failure and periprosthetic fractures because of periprosthetic bone loss are a major concern in total hip arthroplasty (THA). Hardly any clinical data exist on the long-term evolution of bone mineral density (BMD) around uncemented femoral implants. The question to address is whether relevant bone loss continues into third decade around well-fixed uncemented femoral implants. BMD around stable uncemented straight titanium femoral implants was assessed in a longitudinal cohort study. We included 142 hips of 128 patients and measured the development of the periprosthetic BMD using dual-energy X-ray absorptiometry. The baseline measurement was 12 years (t1) after the implantation of an uncemented femoral stem. Follow-up-measurements were performed at 17 (t2) and at 21 years (t3) after primary THA. The regions of interest (ROI) were selected conforming to Gruen et al. We acquired complete data including three consecutive measurements (t1, t2, t3) for 42 patients (49 hips). Performing radiographic evaluation at t1, t2 and t3, we found a regular bone-implant interface present in all cases. Significant decrease in BMD could be shown in ROI 1 (p = 0.0001; − 7.8%), 4 (p = 0.024; − 2.4%), 6 (p = 0.001; − 5.5%) and 7 (p < 0.0001; − 11.7%) between t1 and t3 and in ROI 1 (p = 0.002; − 3.7%), 2 (p = 0.046; − 3.6%), 4 (p = 0.002; − 2.7%) and 7 (p < 0.0001; − 8.0%) between t2 and t3. There were significant differences in overall bone density (netavg) between t1 and t3 (p = 0.001; − 3.6%) and between t2 and t3 (p = 0.020; − 2.1%). The data indicate clinically relevant changes of BMD especially in the proximal Gruen zones in the long-term after uncemented THA. Loss of periprosthetic BMD might be a risk factor for periprosthetic fractures.
Gesehen am 07.02.2020